1980
DOI: 10.1007/bf00454228
|View full text |Cite
|
Sign up to set email alerts
|

The cancellation method for an accurate determination of an air-bone gap

Abstract: For a reliable detection of the bone conduction threshold blocking of the contralateral ear can be necessary but then the noise will affect the threshold in the test ear. To resolve this problem the cancellation method is used. The equalization of air and bone conduction sound level in the inner ear is very accurate, the relation between the intensities has been proved to be linear and independent of noise at the contralateral ear. An application for calibration of the bone conduction vibrator to the head phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The masking may affect the subjects' abilities to achieve optimal cancellation settings. Kapteyn et al (1980) reported that contralateral noise up to 70 dB HL did not disturb their cancellation adjustment. At the highest levels in this study (60 dB HL), the noise level was probably between 70 and 80 dB SPL.…”
Section: Discussionmentioning
confidence: 98%
“…The masking may affect the subjects' abilities to achieve optimal cancellation settings. Kapteyn et al (1980) reported that contralateral noise up to 70 dB HL did not disturb their cancellation adjustment. At the highest levels in this study (60 dB HL), the noise level was probably between 70 and 80 dB SPL.…”
Section: Discussionmentioning
confidence: 98%